Cardioprotective role of β-blockers and angiotensin antagonists in early-onset anthracyclines-induced cardiotoxicity in adult patients: a systematic review and meta-analysis. Issue 1081 (23rd September 2015) - Yun, Seongseok; Vincelette, Nicole D; Abraham, Ivo
ABSTRACT: Background: Anthracyclines are commonly used chemotherapeutic agents with proven efficacy in such malignancies as breast cancer, Hodgkin and non-Hodgkin lymphomas. These agents are associated with irreversible accumulative dose-related cardiomyopathy. Many agents have been examined to reduce cardiotoxicity risk. Aims: We performed a systematic review and meta-analysis to determine the efficacy of β-blockers and angiotensin antagonists to prevent early-onset anthracyclines-induced left ventricular dysfunction and cardiac events. Methods: Relevant articles were searched in PubMed, EMBASE and Cochrane database of systematic reviews up to July 2015. Eligible studies were limited to randomised controlled trials comparing the efficacy of cardioprotective agents (β-blocker and angiotensin antagonist) with control (either no treatment or placebo) in adult patients (age >18 years) treated with anthracyclines-based regimens. Results: Pooled analysis showed an association of β-blockers and/or angiotensin antagonists treatment with higher post-chemotherapy left ventricular ejection fraction (LVEF) of 64.03% compared with 57.48% for control treatment. The mean difference estimate (95% CI) was 6.06% (0.54 to 11.58), p=0.03, with significant heterogeneity, I 2 (95% CI)=96% (82.7 to 109.3). Though the point estimate for the relative rate of cardiac events was lower in the experimental arm, the difference was not statistically significant. In an exploratory subgroup analysis, the benefit of experimental agents on LVEF preservation was prominent in patients treated with higher accumulative dose of anthracyclines, but not in the lower dose group. Conclusions: β-Blockers and angiotensin antagonists treatments were associated with better LVEF preservation, and the benefit was prominent in patients treated with higher anthracyclines accumulative dose. Unexplained heterogeneity remains, indicating the need for more controlled studies. This analysis provides some support for the routine use of β-blockers or angiotensin antagonists in patients undergoing anthracyclines treatment, especially when higher accumulative dose is expected.